W. C. Lubenow, The Politics of Government Growth, Early Victorian Attitudes Toward State Intervention 1833-1848 - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1976)
Recenzja: William C. Lubenow, The Politics of Government Growth, Early Victorian Attitudes Toward State Intervention 1833-1848, [Newton Abbot — Hamden, Connecticut] 1971, David Charles — Archon Books, Library of Politics and Society, II, ss. 238.